Effects of a low-dose combination therapy of zoledronate and dexamethasone on post-tooth extraction socket healing: a pre-clinical study in mice - Ana Julia Moreno BARRETO; Claudia Cristina BIGUETTI; Raquel Barroso Parra da SILVA; Letícia Citelli CONTI; Rafael Carneiro ORTIZ; Alaide GONÇALVES; Edilson ERVOLINO; Antonio Hernandes CHAVES-NETO; Mariza Akemi MATSUMOTO (Journal of Applied Oral Science, 2025)
Abstract Pharmaceutical agents targeting distinct therapeutic pathways can differently influence bone metabolism, notably exemplified by nitrogen-containing bisphosphonates and glucocorticoids. Objective This investigation sought to elucidate the effects of a low-dose administration of zoledronate (ZL) and dexamethasone (DX) on post-tooth extraction sockets healing in a murine model. Methodology In total, 40 young male C57BL/6J mice were assigned to four distinct groups by weight-stratified randomization: Control (C) - 0.9% saline solution, ZL - 0.05 mg/kg ZL, DX - 5 mg/kg DX, and ZL+DX - combined regimen of 0.05 mg/kg ZL and 5 mg/kg DX. All substances were intraperitoneally delivered on a weekly basis from four weeks before right upper incisor extraction and up to seven and 30 days after it, when blood was collected for biochemical analysis of bone markers and the maxillae were removed and prepared for microcomputed analysis of the trabecular architecture of the healing sockets and to set histological slices to be stained with hematoxylin and eosin and immunohistochemistry for TRAP and Runx2. Results Histopathology and microCT showed that DX administration correlated with impaired bone formation, manifesting as reduced bone volume/total volume and trabecular thickness. Conversely, ZL exposure disrupted bone viability. However, the combination of both showed enhanced maturation in bone remodeling at day 30. Notably, DX treatment notably reduced serum calcium and phosphate levels and total TRAP. Runx-2+ cells significantly increased in the Control group at day seven when compared to ZL and DX-ZL and at day 30 when compared to ZL. Conclusions Our findings showed that co-administering low doses of ZL and DX in young male mice augmented the recuperative processes of their post-extraction sockets when juxtaposed with either agent in isolation. Nevertheless, further comprehensive inquiries are needed to delineate the precise underlying mechanisms in a more controlled experimental context.